ANALISIS PENDIDIKAN KRITIS SEBAGAI KONSEP PEMIKIRAN PAULO FREIRE TERHADAP KAUM TERTINDAS - Fakhreji Umam, Diaz (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2026)
This article aims to support Paulo Freire's views regarding education, which are similar to banking-style methods. This research aims to understand the concept of Critical Education, which can serve as a reference, becoming the main aspect when examining the culture of social classes, which are always revolving around the order of social life. Currently, the qualitative research method aims to better explain the objects that will be studied in this research, especially those related to the education of the oppressed and the concept of critical education by Paulo Freire, with authentic facts in his thinking. He assumes critical thinking to have a pattern of protecting the oppressed (Mustadaffin), in this case, very closely related to slaves or small people who are always oppressed. So, in his thinking, Paulo Freire cares about small communities that are always oppressed, especially those without parents (orphans).